From crisis to care: exploring the resilience of pediatric urologists in tackling complex urological challenges in a resource-limited country during volunteer campaigns: a qualitative study - Aboalsamh, Anas; Bassi, Yousef; Khafagi, Dana; AlShamrani, Sarah Ali; AlZahrani, Ahmad A.; Mesawa, Abdullah; Alsaywid, Basim (Frontiers in Public Health, 2025)
Surgeons operating in resource-limited settings encounter unique challenges due to the scarcity of materials and resources. Complex urological disorders (CUDs) such as bladder exstrophy, cloacal exstrophy, and posterior urethral valves, prevalent in these settings, often lead to varying surgical outcomes. This study aims to understand the experiences of surgeons treating pediatric patients with varying CUDs in a setting where resources are scarce through a qualitative phenomenological approach. We conducted six in-depth interviews with six pediatric urologists and surgeons who participated in humanitarian missions sponsored by the King Salman Humanitarian and Relief Center. The interviews, analyzed using the Nvivo v14.23.0 software, revealed common themes: inadequate equipment, lack of trained personnel, infrastructure challenges, emotional and physical tolls, and the need for effective communication and collaboration with local healthcare teams and providers. The findings highlighted the surgeons' adaptive strategies and resilience in overcoming these obstacles, emphasizing the critical role of support from humanitarian organizations. The study underscores the importance of ongoing education for local medical staff, the potential of telemedicine, and the need for consistent presence in resource-limited areas to improve patient care and outcomes. Addressing these challenges requires a concerted effort to optimize resources, enhance training, and support healthcare providers' wellbeing in these demanding environments.